Taurine supplementation enhances anaerobic power in elite speed skaters: A double-blind, randomized, placebo-controlled, crossover study - Buzdağlı, Yusuf; Eyipınar, Cemre; Öget, Furkan; Şıktar, Erdinç; Forbes, Scott; Tekin, Aslıhan (Biology of Sport, 2023)
Taurine (2-aminoethanesulfonic acid) is a semi-essential sulphur-containing amino acid abundant in skeletal muscle. Taurine supplementation is popular among athletes and has been purported to enhance exercise performance. This study aimed to investigate the ergogenic effects of taurine supplementation on anaerobic (Wingate; WanT) performance, blood lactate, ratings of perceived exertion (RPE), and countermovement vertical jump (CMJ) in elite athletes. For this study, randomized, double-blind, placebo-controlled crossover designs were used. Thirty young male speed skaters were randomly assigned to either taurine (TAU; single dose of 6 g) or placebo (PLAC; single dose of 6 g) 60 minutes before testing. Following a 72-hour washout, period participants completed the opposite condition. TAU improved peak (Δ% = 13.41, p < 0.001, d = 1.71), mean (Δ% = 3.95, p = 0.002, d = 1.04), and minimum power output (Δ% = 7.89, p = 0.034, d = 0.48) compared to placebo. Further, RPE (Δ% = -10.98, p = 0.002, d = 0.46) was significantly lower following the WanT in the TAU condition compared to placebo. There were no differences between conditions for the countermovement vertical jump. In conclusion, acute TAU supplementation augments anaerobic performance in elite speed skaters.